An Update of In Vitro Fertilization-Intra Cytoplasmic Sperm Injection: A Review of Sperm Selection Methods - Marianne Ingrid Aror (Journal of Global Pharma Technology, 2020)
In Vitro Fertilization (IVF)-Intra Cytoplasmic Sperm Injection (ICSI) is a well-known infertility management, but the success rate remains low. One of etiologies is the sperm factor. The objective of this review is to explore the update of sperm selection methods for selecting the best sperm quality for IVF-ICSI. Initially, semen analysis should be conducted hence sperm motile and morphology data are obtained. If there is standard sperm morphology in semen analysis, then in the motile sperm organelle morphology (MSOME), important sperm organelles are also obtained, such as nuclues, which are supplemented with vacuole data. Then, due to limitation of semen analysis, the analysis of sperm DNA fragmentation exists to analyze the quality of sperm DNA integrity. Sperm DNA fragmentation is caused by apoptosis. Magnetic Activated Cell-Sorting (MACS) is a sperm selection method that selects non-apoptotic sperms for IVF-ICSI. Finally, Physiological ICSI (PICSI) method is performed to select qualified sperms based on its binding with hyaluronan, immitating the physiological process in natural fertilization. It is important to select the best sperm quality through the most appropriate selection method to increase the success rate of IVF-ICSI. Keywords: IVF-ICSI, Sperm selection, DFI, MSOME, MACS, PICSI.